2022
DOI: 10.3846/bmee.2022.16905
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Consumer Resistance of Mobile Payment During Covid-19: An Interpretive Structural Modeling (Ism) Approach

Abstract: Purpose – Due to country-wise lockdown and state-wise curfews in COVID-19, people were not able to make offline payments (i.e. cash payments) during purchases in India. So, people are switching their payment behavior from offline to online mode. But, as per the central bank report, the rate of adoption through mobile payments is still slow. The paper focuses on identifying critical barriers to mobile payment systems (MPSs) adoption in India. Innovation resistance theory (IRT) has been used as a base model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 112 publications
0
0
0
Order By: Relevance
“…In research conducted by Naveed et al [42], it was found that users experienced a usage barrier in adopting green banking when they found it challenging to use the technology. Besides that, it also needs adjustments and changes from old habits so that it has the potential to hinder adoption [27,28].…”
Section: Usage Barrier (Ub)mentioning
confidence: 99%
See 1 more Smart Citation
“…In research conducted by Naveed et al [42], it was found that users experienced a usage barrier in adopting green banking when they found it challenging to use the technology. Besides that, it also needs adjustments and changes from old habits so that it has the potential to hinder adoption [27,28].…”
Section: Usage Barrier (Ub)mentioning
confidence: 99%
“…In addition, user adoption of technological advances such as online banking also requires technical progress, which requires learning and mastery of the technology [26]. IRT has been researched in various fields to evaluate user resistance to technologies such as mobile banking [27][28][29], virtual shopping [30,31], and mobile commerce [32][33][34]. Based on this explanation, this study aims to explore the functional and psychological barriers experienced by users of green banking technology through the innovation resistance theory approach.…”
Section: Introductionmentioning
confidence: 99%
“…An innovative business requires process modelling, that is, responding quickly to market signals, predicting the effects of decisions constituting an incentive in everyday operation, and taking on the difficulties encountered. Adoption of an adequate business model is essential for STPS (Cardon, Stevens & Potter, 2011;Singh & Singh, 2022).…”
Section: Entrepreneurship Creation Vs Sdgsmentioning
confidence: 99%
“…Even during the current COVID-19 scenario, the ISM technique is used to solve various issues, such as studies conducted by [29][30][31][32][33][34][35] and many others. The study conducted by [29] emphasized the interdependencies of the factors affecting artificial intelligence in the healthcare sector during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by [31] looked into the new management techniques that will allow the market's current demands to be met by the renewable energy industry, especially in the wake of the COVID-19 pandemic's emergence. On the side of the consumer, because they could not make offline payments for purchases in India, because of the COVID-19 pandemic, [32] concentrated on identifying crucial impediments to the adoption of mobile payment systems.…”
Section: Introductionmentioning
confidence: 99%